Effect of body dissatisfaction on binge eating behavior of Chinese university students: A moderated mediation model - Yan, Jimin; Su, Haodong; Li, Chunlu (Frontiers in Psychology, 2022)
The relationship between body dissatisfaction and binge eating behavior has been highlighted by previous studies. However, the psychological mechanisms underlying body dissatisfaction-induced binge eating behavior remain unclear. Here, we further addressed this issue in the framework of the sociocultural model of eating disorders. Firstly, we investigated the mediation effect of perceived stress on the relationship between body dissatisfaction and binge eating. Secondly, we examined the moderation role of the self-acceptance and emotion regulation strategies on the indirect effect of body dissatisfaction on binge eating behavior mediated by perceived stress. Data from 903 Chinese university students were analyzed using SPSS 26.0 and SPSS PROCESS Macro. Results indicated that perceived stress mediates the relationship between body dissatisfaction and binge eating behavior. Main interactional effects have been observed when self-acceptance and cognitive reappraisal but not expressive suppression are introduced in the model as a moderator. Implications and limitations of the study are discussed.